2012
DOI: 10.1620/tjem.226.301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Distinct Gene Expression Profiles between Esophageal Squamous Cell Carcinoma and Adjacent Normal Epithelial Tissues

Abstract: Esophageal squamous cell carcinoma (ESCC) is a predominant type of esophageal cancer, which is a malignant tumor originating from the esophageal mucosa or gland and is aggressive with poor prognosis. Identification of new gene expression patterns would be helpful for providing new targets for the early detection and treatment of ESCC patients. In the present study, we employed cDNA array technology to compare gene expression profiles between ESCC tissues and adjacent normal epithelial tissues from ESCC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The gene expression profile data of Kono et al ( 2009 ) showed that TTK was overexpressed in a large portion (> 90%) of esophageal cancers, while it was almost undetectable in normal organs, except the testis and/or placenta. Similarly, two other studies have shown that TTK mRNA level is increased in esophageal cancer (Tao et al 2012 ; He et al 2018 ).…”
Section: The Expression Of Ttk In Esophageal Cancersupporting
confidence: 55%
See 1 more Smart Citation
“…The gene expression profile data of Kono et al ( 2009 ) showed that TTK was overexpressed in a large portion (> 90%) of esophageal cancers, while it was almost undetectable in normal organs, except the testis and/or placenta. Similarly, two other studies have shown that TTK mRNA level is increased in esophageal cancer (Tao et al 2012 ; He et al 2018 ).…”
Section: The Expression Of Ttk In Esophageal Cancersupporting
confidence: 55%
“…TTK protein kinase (TTK), also called Monopolar spindle 1 kinase (MPS1), is a HLA-A2402-restricted epitope peptide derived from cancer–testis antigens (CTA) (Mizukami et al 2008 ), and it is a previously unidentified member of the kinase family. It can phosphorylate serine, threonine, and tyrosine hydroxyamino acids, and is associated with cell proliferation (Tao et al 2012 ) and cell invasion (King et al 2018 ). It is also a critical regulator of the spindle assembly checkpoint (SAC), which functions to maintain genomic integrity (Thu et al 2018 ) and controls cell fate (Szymiczek et al 2017 ).…”
Section: The Progress Of Lage-1 Molecule In Immunotherapymentioning
confidence: 99%
“…SOX4 also acted as a suppressor in the growth of glioblastoma, partly by activating p53-p21 signaling to induce G0/G1 cell cycle arrest (23). Moreover, SOX4 was found upregulated in ESCC and the SOX-Wnt interaction was identified to be involved in the development of ESCC (24). The specific regulatory mechanism remains to be further explored.…”
Section: Hnf1a-as1 Promotes Growth and Metastasis Of Esophageal Squammentioning
confidence: 99%
“…The SAC thus serves as a safeguard against chromosome missegregation and subsequent aneuploidy. In an apparent contradiction to its role as a checkpoint protein, TTK has been shown to be overexpressed in breast cancer and other solid cancers ( Yuan et al , 2006 ; Salvatore et al , 2007 ; Daniel et al , 2011 ; Tao et al , 2012 ), and RNAi-mediated or pharmacological inhibition of TTK function efficiently attenuated growth of a variety of cancer cell lines ( Colombo et al , 2010 ; Tardif et al , 2011 ). Our own results demonstrate that this also holds true for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%